Geological characteristics and genesis of the Late Carboniferous extremely thick slate in the Shuangjianzishan Ag-Pb-Zn district, southern Great Xing’an Range, NE China: constraints on metallogenesis and tectonic setting - Zhu, Wei-Peng; Tian, Wei; Zhang, Ying-Hui; Li, Zhuang; Gong, Ming-Yue; Fu, Bin; Wang, Zi-Long; Wei, Chun-Jing (Frontiers in Earth Science, 2023)
The Shuangjianzishan super-large Ag-Pb-Zn deposit is situated in the southern Great Xing’an Range (SGXR), which is part of the eastern Central Asian Orogenic Belt (CAOB) and the northeastern Xing’an-Mongolia Orogenic Belt (XMOB). The host rock of this deposit is the Dashizhai Formation, characterized by a widely distributed, extremely thick slate in the Shuangjianzishan basin. Petrographically, the slate contains secondary minerals such as secondary quartz, biotite, sphalerite, pyrite, galena, and chalcopyrite, in addition to primary quartz, feldspar, and rock fragment. The whole-rock geochemical analysis indicates that the slate was deposited in an oxygen-deficient shale basin, influenced by calcium-rich volcanic ash and magmatic-hydrothermal fluids. The mineralogical characteristics of sulfide minerals and the in-situ sulfur isotopic composition of pyrites suggest that the sulfide minerals were likely formed before the primary metallogenic epoch, indicating pre-enrichment of metals. The color variation from black to green observed in the drilling core of the slate is attributed to differences in feldspar content, with the denser “black” slate marking the metallogenic horizon. Based on previous research, it is inferred that the slate is a product of the post-orogenic extensional tectonic setting of the XMOB in the Late Carboniferous, and it underwent alteration by epithermal magmatic-hydrothermal fluids during the Mesozoic metallogenic episode.